Playa Giron = Bay of Pigs : 1961, Washington's first military defeat in the Americas - Castro, Fidel, 1926-2016 (Pathfinder, 2011)
In less than 72 hours of combat during April 1961 near the Bay of Pigs, Cuba's revolutionary militias, police, and armed forces defeated an invasion by 1,500 mercenaries armed, trained, supported, and deployed by Washington. In the process, the Cuban people not only transformed both their country and themselves, they set an example for workers, farmers, and youth across the Americas and the world. With political consciousness, class solidarity, unflinching courage, and a revolutionary leadership that displays an impeccable sense of timing, it is possible to stand up to enormous might and seemingly insurmountable odds -- and win. The example is one that 40 years later the U.S. rulers can still neither accept nor extinguish. With a foreword by Jack Barnes.